Phenotypic diversity of Greek dill (Anethum graveolens L.) landraces. (19th May 2017) - Ninou, Elissavet G.; Mylonas, Ioannis G.; Tsivelikas, Athanasios L.; Ralli, Parthenopi E.
ABSTRACT: Dill has multiple culinary and medicinal purposes and the use of their landraces into a plant breeding program, requires the analysis of their phenotypic diversity. In this study, 33 Greek dill landraces collected from diverse areas were evaluated using traits based on UPOV descriptor list. Phenotypic diversity was assessed using Shannon-Weaver diversity index (H΄) and non-linear principal component analysis. Grouping of landraces was further performed through hierarchical cluster analysis. The H' index ranged from 0.32 (stem waxiness) to 0.98 (density of foliage) with a mean value of 0.68 indicating a high level of phenotypic diversity. High H' values were recorded for the foliage width, stem color and anthocyanin coloration. Multivariate analysis revealed three common genetic groups: 1) North mainland Greece, 2) Aegean islands and 3) Central mainland Greece. The landraces' heterogeneity was attributed to various traits linked to specific geographic origin, such as early time of flowering and high stem waxiness allied with the landraces originated from the Aegean islands. Greek dill landraces revealed useful variation on yield component traits related to fresh herb weight and to seed production, such as high number of leaves/plant and large diameter of main umbel that can be promptly exploited in breeding programs.